Genetic correlations and genome-wide associations of cortical structure in general population samples of 22,824 adults - Edith Hofer (Nature Portfolio, 2020)
Cortex morphology varies with age, cognitive function, and in neurological and psychiatric diseases. Here the authors report 160 genome-wide significant associations with thickness, surface area and volume of the total cortex and 34 cortical regions from a GWAS meta-analysis in 22,824 adults.